Interpretation of Water Quality for Cases with Potential Saline Intrusion - Lazo-Páez, Andrés (2019)
The right water quality data interpretation must be considered, as a main part of the drinking water supply management, and it is also plays a key role in decision making. This situation usually applies when the dissolved solids profile in a specific water sample is completely different from typical behaviors in a specific geographical area. Therefore, the current study introduces a brief methodology that allows the establishment of preliminary water quality criteria, when water is affected by salt water intrusion, or even if it suffers the influence of a geological condition. According to calculations presented in this document, the most adequate indexes for the water quality evaluation are: historical conductivity and chloride trends, Simpson ration, calcium-magnesium ratio, sodium-chloride ratio, ion exchange ratios, and the behavior of the total dissolved solids. These calculations allow the differentiation between a saltwater intrusion condition and other rare situations, such as: hard water, high total dissolved solids concentration, dissolved metals, or even very basic or acidic waters. Even though some other tools might exist, the ones presented in this document can be used as a starting point, with a very robust and science – based background, in order to support the management of drinking water services whose quality faces changes without a clear explanation.